2018
DOI: 10.7717/peerj.4865
|View full text |Cite
|
Sign up to set email alerts
|

Bullying victimization and child sexual abuse among left-behind and non-left-behind children in China

Abstract: BackgroundBullying is one of the most important factors associated with child abuse. However, robust tests supporting the assumption that being bullied can contribute to child sexual abuse (CSA) among left-behind children (LBC) remain sparse. This study aims to investigate the association of bullying victimization with CSA among LBC in China.MethodsA cross-sectional study was conducted in six middle schools of Sichuan and Anhui province in 2015. The bullying victimization was assessed by seven items from the R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 41 publications
1
18
1
Order By: Relevance
“…The children's bullying experience was measured by the Revised Olweus Bully/Victim Questionnaire (4, 8, 35, 36). Of the 40 items, we selected 24 to assess these children's bullying victimization and bullying behaviors.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The children's bullying experience was measured by the Revised Olweus Bully/Victim Questionnaire (4, 8, 35, 36). Of the 40 items, we selected 24 to assess these children's bullying victimization and bullying behaviors.…”
Section: Methodsmentioning
confidence: 99%
“…These children are a special group, as they have a higher risk of psychological and educational problems in rural China, and their growth and development have been of general concern to society. A lacking of parental care and nurturance lead to a higher likelihood of LBC being bullied, attempting suicide, and suffering from abuse (4). A number of studies have examined the associations between parental migration and children's psychological health and social interactions, mostly suggesting an increase in the risks of psychological problems, school bullying, child abuse, and suicide (57).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The extent of bullying exposure appears to be equal in both sexes, however, males are more exposed to physical bullying while females engage in spreading rumors and ostracism [22]. There are many factors associated with bullying victimization such as depression, Internet addiction, physical, sexual, and psychological abuse, psychoactive substance use, domestic violence, low socioeconomic status, a high pressure environment and unstable relations with peers [23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies demonstrated that LBC is much more vulnerable to school bullying or peer/sibling victimization since lack of supervision of parents [5]. Yan and colleagues' study in Sichuan and Anhui province showed 43.31% of the LBC reported high bullying victimization score, while only 37.94% in the non-LBC.…”
Section: Introductionmentioning
confidence: 98%